Deep lamellar keratoscleroplasty for epibulbar dermoids: a case series - O. V. Ivanovska; L. F. Troichenko; G. I. Drozhzhyna; V. L. Ostashevskyi (Journal of Ophthalmology)
Background: Corneal and limbal dermoids are benign congenital tumors which are most commonly located in the inferotemporal quadrant. Tumor growth results in astigmatism, leading to anisometropic amblyopia. It is important to select a surgical treatment option contributing to a reduction in astigmatism and an improvement in visual acuity, and leading to good or excellent cosmetic results. Purpose: To report a case series of epibulbar dermoids treated with deep lamellar keratoscleroplasty. Material and Methods: We report on 4 cases (age range, 14 to 40 years) with epibulbar corneal limbal dermoids (2 eyes) and limbal dermoids (3 eyes). Dermoid excision by deep lamellar keratoscleroplasty was performed in three eyes, and by peripheral lamellar keratoscleroplasty, in one eye. In addition, no surgery was performed in one eye with a grade I dermoid. Patients underwent general eye examination, ocular photography was performed for documentation purposes, and excised dermoids were sent for histomorphological examination. Results: In all cases, histomorphological studies confirmed the benign nature of the disease. In addition, the corneal portion of the corneoscleral graft or the corneal graft was clear. Deep lamellar keratoscleroplasty for corneal and limbal dermoids contributed to a significant reduction in corneal astigmatism, improvement in visual acuity and satisfactory cosmetic results. No corneoscleral graft rejection or neovascularization was noted and no infectious complication was observed.